Violence against women: Public policies and their paths of confrontation in primary care - Freire, Maria Antonia; Souza, Beatriz de Barros (Seven Editora, 2023)
The discussion about inequalities between men and women, as we know, is not recent, being common the belief, in Western history, that women were inferior in the metaphysical scale that divided human beings and, therefore, men held the right to exercise a public life in their place (MARTINS, 2015). Women were always reserved a place of lesser prominence: their rights and duties were always directed to the rearing of children and the care of the home, therefore, to private life, and, during the century of lights, whoever thought he would seize the equality established by the French Revolution to climb spaces in public life would be destined for certain death at the guillotine, many women who tried to claim their citizenship rights met this fate (PARKINS, 2000). DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-156